How Does Narcolepsy Impact Health-Related Quality of Life? A Mixed-Methods Study. Issue 2 (4th March 2021) - Ong, Jason C.; Fox, Rina S.; Brower, Rylee F.; Mazurek, Sophia; Moore, Cameron
ABSTRACT: Study Objectives : The purpose of this study was to identify patient-centered issues affecting Health-Related Quality of Life (HRQoL) in people with narcolepsy (PWN) and to evaluate patient-reported outcome measures using a mixed-methods approach. Methods : Twenty-nine adults (93% female, mean age = 31 years) with an established diagnosis of narcolepsy (Type I = 58.6%) completed focus group interviews using live videoconferencing. Additionally, participants completed the Patient-Reported Outcomes Measurement Information System (PROMIS) measures along with legacy measures commonly used in narcolepsy research (Epworth Sleepiness Scale, Patient Health Questionnaire, Short-Form 36). Results : Thematic analysis of qualitative data revealed that HRQoL was impacted by the constancy of sleepiness, unpredictability of narcolepsy symptoms, and negative public perception of narcolepsy. Challenges to accessibility and/or quality of care included dissatisfaction with non-sleep specialists' understanding of narcolepsy, the unpredictability of symptoms, and the cost of health care. There was enthusiasm for developing a psychosocial intervention to improve HRQoL using online access, but there were mixed opinions regarding the format, provider background, and content of the intervention. Elevations (T-score > 60) were found on PROMIS measures of depression, anxiety, fatigue, and sleep impairment. These patterns were consistent with the levels reported on legacy measures. PWN Type I reported lower levels of general health relative to Type II ( p < .05). Conclusions : These findings lay the groundwork for more targeted efforts to address areas of diminished HRQoL in PWN. Additionally, PROMIS measures appear to be suitable and efficient instruments for assessing HRQoL in PWN.